Análisis de la campaña no más cruces rosadas contra la violencia de género. - Tintin Obando, Evelyn Gabriela (2016)
The main goal of this academic article is to analyze the campaign “No more pink crosses”, which has been led by the city councilwoman Carla Cevallos (Quito, Ecuador) in order to inform and raise awareness among citizens about what gender violence is and how it affects coexistence. First of all, a historical review has been carried out to find the reasons underlying this phenomenon and the efforts made worldwide to decrease its effects. As part of the results, the main message has been studied according to the communication criteria supplied by the Argentinean author Daniel Prieto and other academics within this topic. This research belongs to the exploratory kind because what is being looked for is a first approach to the subject. It has been done in Quito due to the fact that it was promoted by the local government. As far as the image is concerned, it has been analyzed trying to find out the sense given to it, the appellative function it fulfills in the campaign and its relation with the text. Finally, among the most important conclusions that have been gotten, it is possible to state that this initiative did not have a planning by measurable stages; it was rather intended to create controversy from the very beginning leaving aside central elements such as the accountability for gender violence effects and the ways to prevent them.